Survey of Students' Basic Table Tennis Skills Grade V SDN 7 Pinembani - Rustam, Rustam; Hendriana Sri Rejeki; Rahmah; Delvi Kristanti Liloi (The Future of Education Journal, 2026)
This study aims to determine the level of basic table tennis skills in fifth-grade students at SDN 7 Pinembani. Basic table tennis skills in this study were measured through six types of tests: a 30-second bouncing test, a 1-minute forehand stroke test, a 1-minute backhand stroke test, and a 10-time service test. The study subjects were 10 fifth-grade students at SDN 7 Pinembani who were selected as the research sample. The results showed that no students (0%) were in the Very Good category, this was because most students had not been able to master the basic techniques thoroughly and correctly. A total of 3 students (30%) were in the Good category, influenced by their habit of playing table tennis regularly both at school and outside of school. Five students (50%) fell into the Moderate category, characterized by a standard score, where students mastered only one test item well but were weak on the others. Two students (20%) fell into the Poor category, due to low scores on almost all test items and the lack of sports facilities and infrastructure at school, such as limited table tennis rackets, balls, and nets. Furthermore, two students (20%) fell into the Very Poor category, influenced by their low interest in table tennis. Based on these results, it can be concluded that the level of basic table tennis skills of fifth-grade students at SDN 7 Pinembani is mostly in the Moderate category (50%), thus requiring improved learning and the provision of adequate facilities and infrastructure to support basic table tennis skills in elementary schools.